Characterization, activation and reactivity – A case study of Nordic volcanic materials for application as Supplementary Cementitious Materials - Amrita Hazarika; Liming Huang; Sigurdur Erlingsson; Klaartje de Weerdt; Ingemar Löfgren; Sahar Iftikhar; Arezou Babaahmadi (Case Studies in Construction Materials)
Despite their historical importance, the widespread use of volcanic materials as Supplementary Cementitious Materials faces challenges. There exists a knowledge gap relating the properties such as chemical compositions, mineralogy, physical attributes (effective particle size distribution, and specific surface areas) with reactivity. The current study investigates the correlation between noted properties when physical properties are altered by mechanochemical treatments applied to four unique volcanic materials with diverse mineralogy including Albite, Anorthite, Andesine, Oligoclase and Olivine. The alterations in these properties are then linked to changes in the reactivity levels of volcanic materials. The key findings emphasize that grinding volcanic materials for up to 20 min can result in significant improvements. The following outlines the most notable changes observed from 5 min to 20 min: a decrease in D50 from 37 μm to 9 μm, an increase in surface area from 4 m2/g to 13 m2/g, and a rise in average degree of amorphization of the four volcanic materials from 70 % to 83 %. Progressive increases in reactivity levels were observed when extending the milling time from 5 to 20 min, with the most significant increase showing a change from 56 J/g to 350 J/g SCM, as measured with the MR3 reactivity test. X-ray diffraction analyses reveal the detection of new phases like Magnetite and Iron with prolonged mechanochemical activation, and the reaction of mineral phases over time, in MR3 mixes.